Determination of zooplankton dietary shift following a zebra mussel invasion, as indicated by stable isotope analysis - MAGUIRE, CAITRIONA M.; GREY, JONATHAN (Freshwater biology, 2006)
Summary 1. Freshwaters with established zebra mussel populations typically exhibit reduced chlorophyll a concentrations, but the subsequent impacts upon zooplankton are varied. We hypothesised that in an invaded system with less phytoplankton but available allochthonous subsidy, zooplankton may utilise greater proportions of allochthonous matter and that this could be traced by analysis of stable carbon and nitrogen isotopes. 2. We used archived zooplankton samples which had been consistently preserved and which spanned the invasion period of an Irish lake, Lough Erne. Increasing reliance upon allochthonous resources would be reflected in an increase in zooplankton δ13C away from phytoplankton which is relatively 13C‐depleted in humic‐stained L. Erne. 3. Analysis of a series of monthly samples (1992–96, 1999–2003) revealed significant 13C‐enrichment of mixed zooplankton, Eudiaptomus gracilis and Mysis relicta post‐zebra mussel invasion; δ13C values approached −27‰ typical of terrestrial organic matter during spring and autumn. Changes in zooplankton elemental composition also suggested a switch to a lower quality diet. However, analysis of zooplankton δ13C from an annual, single‐point (June) time series spanning 28 years (1977–2004) suggested that when phytoplankton was sufficiently abundant, zooplankton used this resource and their δ13C remained relatively constant around −32‰. Post‐invasion enrichment of mysid δ15N may reflect a shift towards carnivory, but planktonic prey abundance was reduced and a subsequent loss of body condition could result in the same isotopic changes. 4. Our results indicate that in L. Erne, when phytoplankton was reduced by zebra mussel filtering, zooplankton assimilated more from allochthonous matter, and potentially sustained a higher population than would otherwise be possible. Thus, zebra mussel impact on foodweb structure and function is likely to be different in lakes subject to varying subsidy levels.